(untitled) (Journal of Science Foundation, 2016)
Amidst mounting protests both at home and in lower riparian Bangladesh, India is going ahead with the plan to construct its largest and most controversial 1500 mw hydroelectric dam project on the river Barak at Tipaimukh in the Indian state Manipur. In the process, however, little regard is being paid to the short and long-term consequences on the ecosystem, biodiversity or the local people in the rivers watershed and drainage of both upper and low reparian countries. This 390 m length and 162.8 m. high earthen-rock filled dam also has the potential to be one of the most destructive. In India too, people will have to suffer a lot for this mega project. The total area required for construction including submergence area is 30860 ha of which 20797 ha is forest land, 1195 ha is village land, 6160 ha is horticultural land, and 2525 ha is agricultural land. Cconstruction of the massive dam and regulate water flow of the river Barak will have long adverse effects on the river system of Surma and Kushiyara in the north-eastern region of Bangladesh which will obviously have negative impacts on ecology, environment, agriculture, bio-diversity, fisheries, socio-economy of Bangladesh. To assess the loss of Tipaimukh dam on downstream Bangladesh, an Eivironmental Impact Assessment (EIA) has been conducted based on probable affect parametes. Present study intends to depict Tipaimukh dam construction post scenerio in Bangladesh thru assessing probable loss and damage of the Tipaimukh dam construction. The most effective Batelle method of EIA has been applied in this study. It is found -5 scale severity impact will be imposed if the proposed dam is being construct after assessing values of each parameter. Journal of Science Foundation 2015;13(1):3-10 DOI: http://dx.doi.org/10.3329/jsf.v13i1.27827